2006
DOI: 10.1158/1078-0432.ccr-05-2799
|View full text |Cite
|
Sign up to set email alerts
|

RNASEL Gene Polymorphisms and the Risk of Prostate Cancer: a Meta-analysis

Abstract: Purpose: Studies revealing conflicting results on the role of RNASEL polymorphisms Glu265X, Arg462Gln, and Asp541Glu on prostate cancer risk led us to perform a meta-analysis to investigate the association of these polymorphisms and prostate cancer risk. Experimental Design: Relevant studies were selected by searching PubMed from January 1996 to August 2005 using keywords ''RNASEL gene AND prostate cancer.'' For each study, odds ratio (OR) with 95% confidence interval (95% CI) was calculated to estimate the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 29 publications
1
44
0
Order By: Relevance
“…Indeed, several epidemiologic studies have supported the involvement of the RNASEL gene in the prostate cancer etiology (4,5,30,31), whereas other studies do not (9,22,34,43). Some studies have reported that individuals with a single mutated copy of the RNASEL gene have a 50% increased risk for prostate cancer, whereas those with homozygous mutant RNASEL alleles have a 2-fold-increased risk of prostate cancer (5).The RNASEL gene encodes for the RNase L protein, a constitutively expressed latent endoribonuclease, which mediates the interferon-inducible 2-5A system against viral and/or cellular double-stranded RNAs (8,16,20,23,49,50). The RNase L "Q" variant allele (R462Q) shows a 3-fold decrease in catalytic activity compared to the wild-type enzyme (5, 44).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, several epidemiologic studies have supported the involvement of the RNASEL gene in the prostate cancer etiology (4,5,30,31), whereas other studies do not (9,22,34,43). Some studies have reported that individuals with a single mutated copy of the RNASEL gene have a 50% increased risk for prostate cancer, whereas those with homozygous mutant RNASEL alleles have a 2-fold-increased risk of prostate cancer (5).The RNASEL gene encodes for the RNase L protein, a constitutively expressed latent endoribonuclease, which mediates the interferon-inducible 2-5A system against viral and/or cellular double-stranded RNAs (8,16,20,23,49,50). The RNase L "Q" variant allele (R462Q) shows a 3-fold decrease in catalytic activity compared to the wild-type enzyme (5, 44).…”
mentioning
confidence: 99%
“…The RNASEL gene encodes for the RNase L protein, a constitutively expressed latent endoribonuclease, which mediates the interferon-inducible 2-5A system against viral and/or cellular double-stranded RNAs (8,16,20,23,49,50). The RNase L "Q" variant allele (R462Q) shows a 3-fold decrease in catalytic activity compared to the wild-type enzyme (5, 44).…”
mentioning
confidence: 99%
“…We did not assess complete coverage of potential variation across the RNASEL gene. Although we chose to sequence three RNASEL SNPs based on previous study findings (16,19,(35)(36)(37), including two known missense mutations, the mechanism by which rs12757998 may act to increase circulating inflammatory mediators or impact radiation-response remains unknown, and this variant could potentially be a marker for the true causal variant. Also, although there were relatively few men who developed lethal prostate cancer, we cannot exclude the possibility that our inability to detect a statistically significant association between rs12757998 and lethal cancer was not the result of a differential biologic effect rather than a lack of power.…”
Section: Discussionmentioning
confidence: 99%
“…These SNPs were selected based on previously established functional significance (16,19,(35)(36)(37). Genotyping was performed in a blinded fashion after extraction of DNA from whole blood using a standard QIAmp kit (QIAGEN Inc. Chatsworth, CA) protocol using Biotrove Open Array SNP Genotyping Platform at the Harvard Medical School -Partners Healthcare Center for Genetics and Genomics.…”
Section: Genotype Assessmentmentioning
confidence: 99%
“…The RNASEL is expressed by the RNASEL gene localized on the chromosome 1q24-25 (HPC-1), a region for hereditary prostate cancer (3). In some studies a significant relationship has been demonstrated between the chromosome 1q24-25 (HPC1) and prostate cancer risk (4). RNASEL, a role playing gene in regulating cell proliferation, apoptosis and tumor-suppressor cell, is one the candidate genes within the HPC1 region (5).…”
Section: Introductionmentioning
confidence: 99%